Uterine Perforation & Abortion- A Case Report - Sultana, Mst Atia; Uddin, Rakib; Hussain, Rubiyat Farzana; Khatun, Masuma (KYAMC Journal, 2017)
Sreemoti Ratna Sarker 30 years old lady presented to us with the complaints of amenorrhea for 5 months, lower abdominal pain for 5 days, slight per vaginal bleeding for 2-3 days, a cord like structure is coming down p/v on the day of admission. On general examination she was stable and on p/v examination there was cord prolapse. A gentle traction was given and it was expelled out along with a small piece of placental tissue without any fetal parts and bleeding. Then she was advised for USG of abdomen. USG reported a fetus like structure in the abdominal cavity and the empty uterine cavity . She was managed surgically. Now she is doing well. KYAMC Journal Vol. 5, No.-1, Jul 2014, Page 491-493